Case‐crossover study design in pharmacoepidemiology: systematic review and recommendations. (13th September 2013) - Consiglio, Giulia P.; Burden, Andrea M.; Maclure, Malcolm; McCarthy, Lisa; Cadarette, Suzanne M.
ABSTRACT: Purpose: The purpose of this study is to systematically identify and review articles that use the case‐crossover study design in the area of pharmacoepidemiology. Methods: A systematic search ofMEDLINE ® (Ovid Technologies, New York City, NY, USA), EMBASE ® (Elsevier Inc., Philadelphia, PA, USA), and Web of Science® (Thomson Reuters, New York City, NY, USA) was completed to identify all English language articles that applied the case‐crossover study design in the area of pharmacoepidemiology. The number of reviews, methodological contributions, and empirical pharmacoepidemiologic applications were summarized by publication year. Empirical applications were retrieved, and methodological details (outcome, exposure, exposure windows, sensitivity analysis, statistical reporting) were tabulated and compared to methodological recommendations based on exposure characteristics, exposure windows, and discordant pairs data display. Results: Of 836 unique articles identified, 99 pharmacoepidemiologic studies were eligible: 20 methodological contributions, 9 review papers, and 70 empirical applications. Only three empirical applications in the area of pharmacoepidemiology were published before 2000. Since 2000, the number of empirical pharmacoepidemiologic applications published annually has generally increased over time, to before a high of 15 published in 2011. The design was mainly applied to examine drug safety (96%), and most applications investigated: psychotropic (24%) and analgesic (17%) exposure drug classes; and considered hospitalization (23%) and cardiovascular/cerebrovascular (21%) events. Only 31% of applications displayed sufficient data to enable readers to confirm odds ratios presented. Conclusions: Use of the case‐crossover design in pharmacoepidemiology has increased rapidly in the last decade. As the application of the case‐crossover design continues to increase, it is important to develop standards of practice, especially for display of data. Copyright © 2013 John Wiley & Sons, Ltd.